Use of Force Citizen Complaints, Use of Force Violations, and Early Intervention - Hymon, Drema Ann (2020)
Abstract Mounting public protests, increasing expensive payouts, and shootings of unarmed victims by police is a call to reexamine options to problem solving, service recovery, and preventing police misconduct as it pertains to the use of force. The purpose of this quantitative study was to examine the correlation between early intervention system data (a) use of force, citizens' complaints (race and gender), and use of force violations (race, gender, and years of service for officers). The disruptive theoretical framework provided an innovative lens to examine police misconduct of a large midwestern large law enforcement agency. This secondary data study did not find significant relationships between stated variables using chi-square analyses. Although consistent with other studies, males were found likely victims of excessive use of force (X2 = 114.093, p =.000) using multiple regression. By expanding the characteristics of basic variables based on a (use of force) continuum model, the data can be treated as a disruptor with potential to reach maintenance or high productivity and sustainability. The fields of healthcare and education have made strides using this model, and this model may also add to the existing knowledge to create greater transparency, service recovery, and policy modification needed to reduce the use of force police misconduct. As society changes with varying political mandates, public opinions and technological communications, it is apparent that law enforcement must also continually improve efforts to enhance accountability and transparency relating to the use of forc